Molecular genotyping of Indian blood group antigens amongst regular voluntary blood donors of Surat city, Gujarat, India. (April 2022) - Shah, Avani; Patel, Parizad; Jariwala, Keyuri; Qureshi, Farzin; Mishra, Kanchan; Bharadva, Sumit; Ghosh, Kanjaksha
Abstract: Background: There is paucity of data related to the prevalence of the rare blood group antigens amongst South Gujarat blood donor population due to unavailability and high cost of antisera. Therefore it is difficult to screen donors for such rare antigens by gold standard haemagglutination assay. The single nucleotide polymorphism (SNPs) of In a and In b antigens is the base of the PCR based detection methods that help to detect these alleles in regular voluntary blood donors. Materials & methods: Blood samples of 200 unrelated regular voluntary blood donors wee collected. DNA was extracted using phenol-chloroform method and genotyped for Indian (In a / IN*01, In b / IN*02 ) blood group alleles by Sequence Specific PCR. In a antigen positivity was confirmed by serology test. Results: Four donors were found heterozygous for In a antigen i.e. In (a + b+) by SS-PCR and their In a positivity were confirmed by in-house polyclonal Anti-In a reagent. SS-PCR was standardized using known heterozygous sample of a blood donor. The frequency of In a antigen (2.0 %) was higher than Caucasians, lower than Iranians and Arabs while comparable to those reported among Indians of Mumbai city. Conclusion: In absence or unavailability of antisera particularly for low frequency alleles like In a, such PCR based method would be extremely helpful to prepare rare donor registry by screening blood donors' at large scale. Red cells of In a positive donors can be used as in-house reagent red cells for screening and identification of corresponding antibody.